Maritime security: The EU’s discourse on Brazil and the South Atlantic - Ribeiro, I. M. (The Palgrave handbook on geopolitics of Brazil and the South Atlantic, 2025)
The European Union’s (EU) discourse on maritime security has gained prominence in recent years, especially following the adoption of the Strategic Compass in 2022 and the update of the EU Maritime Security Strategy in 2023. Despite the attention given to the North Atlantic due to the EU’s geographic positioning and enhanced cooperation with the North Atlantic Treaty Organization (NATO), the South Atlantic is becoming more prominent in the EU’s discourse with a focus on maritime security and cooperation. One of the most noticeable actors in this context is Brazil, with its significant maritime area of responsibility, which comprehends critical sea routes, ample resources, and a vast exclusive economic zone. Its strategic geopolitical positioning renders Brazil a key player not only in the field of maritime security but also in trade and in the overall stability of the South Atlantic region. Moreover, Brazil has been investing in improving maritime security in the South Atlantic, in line with the EU’s efforts and focus on multilateralism. Despite its limited resources and the lack of a cohesive regional security framework, Brazil has been modernising its own naval capabilities while also engaging with other partners from the South Atlantic in conducting joint exercises and patrols, oftentimes not only in the context of capacity-building initiatives but also in the sharing of information and in countering illicit activities at sea. Considering the increasing importance of the South Atlantic, Brazil’s growing strategic significance, as well as the importance of discourse for the understanding and building of international geopolitics, this chapter seeks to answer the following research questions: How does the EU discursively frame and construct its strategic view of the South Atlantic and its own role therein in the context of maritime security? How does the EU discursively construct Brazil’s role in this context, as an actor of strategic significance for regional maritime security? Anchored in critical geopolitics, this analysis focuses on the EU’s discourse and thus on its own interests and perspective regarding the South Atlantic and Brazil. Furthermore, engaging in a discourse analysis since the establishment of the first EU Maritime Security Strategy in 2014 until its update in 2023 will allow us to explore the semiotic evolution of the EU’s understanding of maritime security, of the South Atlantic, and of Brazil’s role in this context, highlighting the key narratives used and enhancing the body of knowledge on maritime security, on Brazil’s regional actorness, and on the “spatialization” of EU foreign policy discourse.